VIRTUAL EVALUATION OF ANAEMIA– SIMPLE TECHNIQUE - K. Rajamanickam; V. leela; K. loganathasamy; Bhaskaran Ravi latha; M. Balagangatharathilagar; S. Vairamuthu (Indian Journal of Veterinary and Animal Sciences Research, 2023)
Anaemia is one of the major clinical manifestations seen in various diseases in canines. Reticulocytes and erythrocyte counting are the hallmark for evaluating the anaemic status and bone marrow response to anaemia. In this study, a simple technique was developed and followed to count both reticulocytes simultaneously with the help of Neubauer counting chamber using the diluting fluids prepared from two different supravital stains to score the merit of the method for adoption. Blood samples for the study were  collected from the dogs presented to Madras Veterinary College Teaching hospital. The dogs were classified into apparently healthy and anemic group with each of 30 dogs. The total erythrocytic count was significantly low in the anomalous group compared to the healthy group (p